Workplace Attachments : Managing Beneath the Surface. - Grady, James (Routledge Research in Employment Relations Ser., 2019)
How fast can your organization change? How long does it take to adopt new technology? Do things run the same when you bring in a new leader? How does the culture evolve with new acquisitions? There is an underlying thread in all these questions. Workplace attachment or our instinctual (biological) response to attach to both tangible and intangible objects continuously throughout life. Workplace Attachments: Managing Beneath the Surface provides the first comprehensive review of attachment in the workplace. We explore the biological and evolutionary roots of our attachments, explain how you can find attachment behaviour in your workplace, and help you proactively understand attachment behaviour with your team. Our practical research, case studies, and story-telling will help you understand how attachment behaviour impacts you, your employees, your peers and ultimately the culture of your organization. Once you understand how people attach, detach, and re-attach to objects and elements of your organization, you will be able to real and lasting change.